The Correlation Between Student Perceptions of the Use of E-Modules with Students' Basic Science Process Skills - Darmaji, Darmaji; Kurniawan, Dwi Agus; Astalini, Astalini; Winda, Febrina Rosa; Heldalia, Heldalia; Kartina, Lia (JPI (Jurnal Pendidikan Indonesia), 2020)
This study aims to analyze the correlation of students' perceptions of e-module toward students' basic science process skills. The subject of the study were second semester students of Department of Physics Education in Universitas Jambi. This research used a mixed-method research with data collection instruments consisting of student perception questionnaire, observation sheet of students' science process skills, and also interviews. From the results of data analysis, students' perceptions were in the good category with an average of 74.95, and the basic science process skills of students were also in the good category with an average of 69.08. Based on the correlation test conducted there is a significant relationship between the level of student perception of e-module with students’ basic science process skills using Pearson correlation values 0,927, and Sig. (2-tailed) 0.00 at a significance of 1%.